Path analysis of factors associated with nurses’ pain management practices in older adults with cognitive impairment: A cross-sectional study - Phichpraorn Youngcharoen; Atsadaporn Niyomyart; Piyawadee Thongyost; Joachim G. Voss (PLoS ONE, 2026)
Background Pain management is essential, yet inadequate management is linked to anxiety, depression, and poor quality of life. Evidence in Thailand is limited for older adults with cognitive impairment. This study examined factors associated with pain management practices among nurses. Design Secondary descriptive correlational study. Methods A secondary cross-sectional analysis used an existing dataset (1 September-27 October 2023); no new data were collected. Institutional Review Board approval was obtained on 4 February 2024; the dataset was accessed on 5 February 2024. Guided by Social Cognitive Theory, 174 full-time registered nurses completed self-administered paper questionnaires, including a modified version of the Tool for Evaluating the Ways Nurses Assess Pain, the Collaboration and Satisfaction Care Decisions Instrument, and the Pain Management Self-Efficacy Questionnaire. Data were analyzed using descriptive statistics, Spearman’s correlation, and structural equation modeling. Results All nurses were female; most held a bachelor’s degree (95.40%); mean age 31.47 ± 6.98 years. The model showed good fit and explained 37% of the variance in nurses’ pain management practices. Direct effects on nurses’ pain management practices were observed for nurses’ perceptions of collaboration with physicians (β = 0.28, p < 0.001, 95% CI [0.16, 0.41]) and nurses’ pain management self-efficacy (β = 0.34, p < 0.001, 95% CI [0.20,0.47]). Nurses’ knowledge and attitudes toward pain management, nurses’ perceptions of collaboration with physicians, and years of nursing experience also had indirect effects on nurses’ pain management practices through nurses’ pain management self-efficacy (β = 0.08, p < 0.05, 95% CI [0.02, 0.14]), β = 0.08, p < 0.01, 95% CI [0.03, 0.13], and β = 0.13, p < 0.01, 95% CI [0.05, 0.20], respectively. Conclusions Pain management self-efficacy plays a key role in nursing practice. Building it through targeted interventions, training, and institutional support may improve pain management competencies for older adults with cognitive impairment.